Perception of speech sounds in school-aged children with speech sound disorders - Preston, Jonathan L.; Irwin, Julia R.; Turcios, Jacqueline (Seminars in Speech and Language, 2015)
Children with speech sound disorders may perceive speech differently than children with typical speech development. The nature of these speech differences is reviewed with an emphasis on assessing phoneme-specific perception for speech sounds that are produced in error. Category goodness judgment, or the ability to judge accurate and inaccurate tokens of speech sounds, plays an important role in phonological development. The software Speech Assessment and Interactive Learning System, which has been effectively used to assess preschoolers' ability to perform goodness judgments, is explored for school-aged children with residual speech errors (RSEs). However, data suggest that this particular, task may not be sensitive to perceptual differences in school-aged children. The need for the development of clinical tools for assessment of speech perception in school-aged children with RSE is highlighted, and clinical suggestions are provided.
16 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/110-366-030-100-745 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Child; Female; Humans; Male; Phonetics; Speech; Speech Perception; Speech Sound Disorder; Speech sound disorder; assessment; child; dept.cmd; dept.psy; female; human; male; pathophysiology; phonetics; speech; speech perception; speech sound disorder

Ways of examining speech acts in young african american children: considering inside-out and outside-in approaches. - Dejarnette, Glenda; Rivers, Kenyatta O; Hyter, Yvette D (Topics in Language Disorders, 2015)
To develop a framework for further study of pragmatic behavior in young children from African American English (AAE) speaking backgrounds, one aspect of pragmatic behavior is explored in this article, specifically, speech acts. The aims of this article are to (1) examine examples of how external taxonomies (i.e., an “etic” or “outside-in” approach) have been applied to the speech act behavior of AAE child speakers and to note that etic approaches alone do not identify cultural characteristics that influence the presentation of speech acts in this population; (2) conceptualize a culture-sensitive framework where components of AAE speech act behaviors can be identified as gleaned from existing linguistic research; and (3) explain the utility of analyses of speech act behavior using taxonomies that have emerged from the cultural language style of AAE speakers, that is, an “emic” or “inside-out” approach.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/019-681-907-287-000 tex.type: [object Object]
Keywords: English speakers; communicative functions; dept.cmd; language behavior; pragmatic behavior; speech acts; young African American

Pragmatic language of african american children and adolescents: A systematic synthesis of the literature. - Hyter, Yvette D; Rivers, Kenyatta O; Dejarnette, Glenda (Topics in Language Disorders, 2015)
Purpose: A systematic review and synthesis was performed on published articles and dissertations produced between 1970 and 2013 that focused on selected pragmatic language behaviors of African American children and adolescents. Methods: Electronic databases and hand searches of articles located in the databases were used to identify the published articles and dissertations. Each article or dissertation was reviewed by at least 2 of the authors to determine whether it met the criteria for inclusion in this study. Selected observations of the documents that met criteria for inclusion were recorded on the Primary Research Appraisal Tool (PRAT; DeJarnette, Hyter, & Rivers, 2012), a data gathering and analysis framework developed by the authors specifically for this systematic synthesis. Results: The literature search resulted in 92 research articles and dissertations, 37 of which were eliminated because they did not meet all of the inclusion criteria. The documents that met our inclusion criteria focused primarily on the structure and/or content of narrative discourse rather than speech acts, other forms of discourse (e.g., conversation, expository), and presupposition/perspective taking skills. Six major themes identified in the major findings are used to summarize studies reviewed for this systematic synthesis. Conclusions: We (a) explain the current state of knowledge about African American pragmatic language behaviors, (b) explain major findings and implications of the extant literature in this topical area and how it may inform speech-language pathology practice, and (c) identify directions for future research on pragmatic language of African American children and adolescents.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/151-173-234-950-684 tex.type: [object Object]
Keywords: African American; communication functions; dept.cmd; discourse; pragmatic language; presupposition; speech acts; systematic review and synthesis; theory of mind

Phonological complexity in school-aged children who stutter and exhibit a language disorder. - Wolk, Lesley; LaSalle, Lisa R (Journal of fluency disorders, 2015)
PURPOSE: The Index of Phonological Complexity and the Word Complexity Measure are two measures of the phonological complexity of a word. Other phonological measures such as phonological neighborhood density have been used to compare stuttered versus fluent words. It appears that in preschoolers who stutter, the length and complexity of the utterance is more influential than the phonetic features of the stuttered word. The present hypothesis was that in school-age children who stutter, stuttered words would be more phonologically complex than fluent words, when the length and complexity of the utterance containing them is comparable. School-age speakers who stutter were hypothesized to differ from those with a concomitant language disorder., METHODS: Sixteen speakers, six females and ten males (M age=12;3; Range=7;7 to 19;5) available from an online database, were divided into eight who had a concomitant language disorder (S+LD) and eight age- and sex-matched speakers who did not (S-Only)., RESULTS: When all stuttered content words were identified, S+LD speakers produced more repetitions, and S-Only speakers produced more inaudible sound prolongations. When stuttered content words were matched to fluent content words and when talker groups were combined, stuttered words were significantly (p<=0.01) higher in both the Index of Phonological Complexity and the Word Complexity Measure and lower in density ("sparser") than fluent words., CONCLUSIONS: Results corroborate those of previous researchers. Future research directions are suggested, such as cross-sectional designs to evaluate developmental patterns of phonological complexity and stuttering plus language disordered connections., EDUCATIONAL OBJECTIVES: The reader will be able to: (a) Define and describe phonological complexity; (b) Define phonological neighborhood density and summarize the literature on the topic; (c) Describe the Index of Phonological Complexity (IPC) for a given word; (d) Describe the Word Complexity Measure (WCM) for a given word; (e) Summarize two findings from the current study and describe how each relates to studies of phonological complexity and fluency disorders. Copyright © 2014 Elsevier Inc. All rights reserved.
12 citations (Crossref) [2023-10-31] Place: United States Wolk, Lesley. Southern Connecticut State University, Department of Communication Sciences and Disorders, 501 Crescent St, New Haven, CT 06515, United States. Electronic address: Lesleywolk@sbcglobal.net. LaSalle, Lisa R. Communicative Disorders, University of Redlands, 1200 E Colton Ave., Redlands, CA 92373, United States.
Keywords: *Language; *Linguistics; *Phonetics; *Stuttering; Adolescent; Adult; Article; Child; Concomitant disorders; Female; Humans; Language; Language disorders; Linguistics; Male; Phonetics; Phonological complexity; Schools; Speech; Speech Production Measurement; Stuttering; adolescent; adult; child; controlled study; data base; dept.cmd; female; fluency disorder; human; language; language disability; linguistics; male; phoneme; phonetics; school; school child; speech; speech analysis; stuttering

Development of an audiovisual speech perception app for children with autism spectrum disorders - Irwin, Julia; Preston, Jonathan; Brancazio, Lawrence; D'Angelo, Michael; Turcios, Jacqueline (Clinical Linguistics & Phonetics, 2015)
Perception of spoken language requires attention to acoustic as well as visible phonetic information. This article reviews the known differences in audiovisual speech perception in children with autism spectrum disorders (ASD) and specifies the need for interventions that address this construct. Elements of an audiovisual training program are described. This researcher-developed program delivered via an iPad app presents natural speech in the context of increasing noise, but supported with a speaking face. Children are cued to attend to visible articulatory information to assist in perception of the spoken words. Data from four children with ASD ages 8-10 are presented showing that the children improved their performance on an untrained auditory speech-in-noise task.
16 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/022-073-168-350-692 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Attention; Audiovisual Aids; Audiovisual app; Autism spectrum disorder; Child; Child Development Disorders; Pervasive; Comprehension; Humans; Lipreading; Male; Mobile Applications; Pattern Recognition; Visual; Phonetics; Semantics; Speech Perception; Speech perception; attention; audiovisual aid; child; comprehension; dept.cmd; dept.hls; dept.psy; human; lip reading; male; mobile application; pattern recognition; phonetics; psychology; semantics; speech perception